Determinasi Sumber Daya Manusia, Modal Usaha dan Pemasaran Terhadap Perkembangan UMKM Tas - Diah Kurniati; Indri Murniawaty; Nina Farliana (Universitas PGRI Madiun, 2021)
The aimed of this study is to determine there is a partial and simultaneous effect between human resources, business capital, and marketing on the development of micro small and medium enterprises of bags in Jati subdistrict, Kudus regency. The population of this study was bags entrepreneurs in Jati subdistrict, Kudus regency by using a sampling technique that wasproportionate stratified random sampling. The data collection methods used were interviews, questionnaires and documentation, while the data analysis techniques used were descriptive statistical analysis, classical assumption tests, and multiple linear regression analysis. The results show that (1) there is a significant effect of human resources on the development of micro small and medium enterprises of bags in Jati Subdistrict, Kudus Regency in the amount of 9.80%. (2) there is a significant effect of business capital on the development of micro small and medium enterprises of bags in Jati Subdistrict, Kudus Regency in the amount of 16.73%. (3) there is a significant effect of marketing on the development of micro small and medium enterprises of bags in Jati Subdistrict, Kudus Regency in the amount of 7.45%. (4) there is a significant effect of human resources, business capital, and marketing on the development of MSME of bags in Jati Subdistrict, Kudus Regency in the amount of 83.3%.